3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6
-2x^4+16 +2x^4+9-3x^5=-3x^5+25. There is no "answer" because there is no equation.
5x + 4 - 3x + 5 + 2x - 9 = 4x
Firstly, write it as a mathematical equation:3x + 6 = 2x + 10Subtract 6 from both sides:3x = 2x + 4Subtract 2x from both sides:x = 4
5x-2x-3x+4x = (5-2-3+4)x = 4x
To simplify an equation is to combine like terms, but you do not solve it for example: simplify 3X+4-X-6 2X-2
x - 3x + 4 = 3 - 9 simplify -2x + 4 = -6 -4 -4 -2x = -10 /-2 /-2 x = 5
3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x + 2) - 4(x + 2) = (x + 2)(3x - 4).
-6x2 + 17x -12. To get the solution, we set up the formula as follows: (2x - 3) * (4 - 3x) Then we multiply each of the components as follows: (2x * 4) + (2x * -3x) + (-3 * 4) + (-3 * -3x) Then we simplify as follows: 8x + -6x2 + -12 + 9x -6x2 + 17x + -12 -6x2 + 17x -12
Collect like terms together: 3x - 7 - 4 - x = (3x - x) + (-7 - 4) = (3 - 1)x + (-11) = 2x - 11
3x - 2x + 4 = 0 3x - 2x = -4 x = -4
If 3X - 4 ------ = 0 1-2X-4 So 3X - 4 ----- = 0 [ x (2X-3) ] 2X-3 3X-4 = 2X-3 [ -2X ] X - 4 = -3 [ +4 ] X= 1
I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.
3x+56 = 2x+4 3x-2x = 4-56 x = -52
3x+4 = 2x-3 3x-2x = -3-4 x = -7
2x
2x